The safety of inactivated influenza vaccines in pregnancy for birth outcomes: a systematic review. Issue 3 (4th March 2019) - Giles, Michelle L.; Krishnaswamy, Sushena; Macartney, Kristine; Cheng, Allen
ABSTRACT: Pregnant women are at increased risk of morbidity and mortality from influenza and are recognized as a priority group for influenza vaccination. Despite this, uptake is often poor and one reason cited for this is concerns about safety. The objective of this study was to perform a systematic review of the safety of inactivated influenza vaccination (IIV) in pregnancy. Studies were included if they were: (i) observational or experimental design; (ii) included a comparator group comprising of unvaccinated pregnant women; (iii) comprised of either seasonal IIV or monovalent H1N1 IIV (including adjuvanted vaccines); and (iv) addressed one of the following outcomes: preterm birth (PTB), small for gestational age (SGA), fetal death (including stillbirth or spontaneous abortion), low birth weight (LBW) or congenital abnormalities. Two reviewers screened abstracts and titles and selected full texts for retrieval. Crude odds ratios were calculated from reported event rates, using binomial standard errors. Adjusted odds ratios, hazard ratios and relative rates were extracted as reported in each paper. After removal of duplicates and full text eligibility assessment, 40 studies remained. The aOR for PTB was 0.87 (0.78–0.96), for LBW 0.82 (0.76–0.89), congenital abnormality 1.03 (0.99–1.07), SGA 0.99 (0.94–1.04) and stillbirth 0.84 (0.65–1.08). This study contributes to the increasing body of safety data for IIV in pregnancy and reports a protective effect on PTB and LBW.